Workshop on Game Mediated Language Teaching for English Teachers of Senior High Schools in Amuntai, Hulu Sungai Utara Regency - Ahmad Kailani; Dina Rafdiyah; Rezqan Noor Farid (Comment: an International Journal of Community Development, 2019)
Learning English is indispensable from the use of games as one of the teaching media. Even, in traditional classes, where teachers are the center of information, games are sometimes introduced and played to make the classroom atmosphere more fun. Now, as the rapid growth of information technology. The forms and types of games have also evolved significantly. This is like two sides of the coin which has both positive and negative impacts on students’ learning motivation. However, this community service report just looks at the benefits of the game in the English classroom and its feasibility to be used as a catalyst to make students engaged in learning English grammar. This community service was conducted in SMAN 1 Amuntai as the host. Teachers of English from around Amuntai regency were invited to come and introduced to use Kahoot as a learning tool. They were taught how to design quizzes and exercises about grammar using this game application. The participants enjoyed it and would plan to use it as learning media for their English classes.